Chronicity of high and low level mupirocin resistance in Staphylococcus aureus from 30 Indian hospitals - Rajni Prakash; Amar Garg; Riteshkumar Arya; R. K. Kumawat (Scientific Reports, 2023)
Abstract Mupirocin is one of the most effective topically used antibiotic for the treatment of dermatitis, nasal carriage, decolonization of methicillin susceptible Staphylococcus aureus and eradication of methicillin resistant Staphylococcus aureus. Extensive use of this antibiotic has resulted in mupirocin resistance in Staphylococcus aureus which is a matter of concern. This study was conducted to evaluate the high and low level of mupirocin resistance in Staphylococcus aureus collected from various Indian hospitals. A total of 600 samples, of which 436 were pus specimens and 164 wound site swabs were collected from 30 Indian hospitals. Disc diffusion and agar dilution methods were used to test mupirocin susceptibility in methicillin resistant Staphylococcus aureus. Out of 600 Staphylococcus aureus isolates, 176 isolates (29.33%) were found to be methicillin resistant Staphylococcus aureus (MRSA). Out of 176 non-duplicate MRSA strains, 138 isolates were found to be mupirocin sensitive, 21 isolates had high level resistance whereas 17 isolates had low level resistance to mupirocin, which contributed 78.41%, 11.93% and 9.66% respectively. Multidrug resistant susceptibility was tested for all the MRSA with Cefuroxime, Cotrimoxazole and Vancomycin antibiotics. All the high and low level resistant strain were subjected to genome screening for mupA ileS gene respectively. mupA gene was found positive in all the high level resistant strain and out of 17 low level resistant strain, 16 strain were found point mutation in V588F of ileS gene. Overall, high rate of mupirocin resistance was found in the studied samples which might be a result of indiscriminate use of mupirocin in the population of studied region. This data emphasizes the urgent need for formulation of a well-defined and regulated guidelines for mupirocin use. Moreover, continuous surveillance is needed for the use of mupirocin and routine test should be performed to detect MRSA in patients and health care personnel to prevent MRSA infections.